2023
DOI: 10.1002/mp.16319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MR‐guided radiotherapy accumulated doses for central lung tumors with non‐adaptive and online adaptive proton therapy

Abstract: Background: Stereotactic body radiation therapy (SBRT) of central lung tumors with photon or proton therapy has a risk of increased toxicity. Treatment planning studies comparing accumulated doses for state-of -the-art treatment techniques, such as MR-guided radiotherapy (MRgRT) and intensity modulated proton therapy (IMPT), are currently lacking. Purpose: We conducted a comparison of accumulated doses for MRgRT, robustly optimized non-adaptive IMPT, and online adaptive IMPT for central lung tumors. A special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Conversely, we are currently investigating dosimetry benefits and clinical outcomes of online plan adaption in our cohort of patients treated exclusively to ultra-(central) locations. The results of this analysis and further investigations at the level of accumulated dose using the approach by Rabe et al would certainly be of interest and could complement the current literature and aid in future clinical decision making in this setting [51] .…”
Section: Discussionmentioning
confidence: 78%
“…Conversely, we are currently investigating dosimetry benefits and clinical outcomes of online plan adaption in our cohort of patients treated exclusively to ultra-(central) locations. The results of this analysis and further investigations at the level of accumulated dose using the approach by Rabe et al would certainly be of interest and could complement the current literature and aid in future clinical decision making in this setting [51] .…”
Section: Discussionmentioning
confidence: 78%
“…The DSCs of neural network segmentations applied to 3D-MRI acquisitions using fast ultra-short echo time sequences were higher than those of our algorithm. DSCs of 0.97 with a 95 %-CI [0.96, 0.97] for the right lung and 0.96 with a 95 %-CI of [0.96, 0.97] for the left lung were found in [42] using manual segmentations complemented by the region growing algorithm of [38] as reference. In [44] a total DSC of 0.967 ± 0.076 was observed for lung tissue when using manual segmentation by an experienced radiologist as a reference.…”
Section: Discussionmentioning
confidence: 99%
“…Our MRI-based study has shown that TLC conditions under eDIBH provide excellent reproducibility of lung topology, including potential tumor locations and adjacent structures [21] . Accurate LV determination by reliable, effective contouring is paramount to accurately quantify e.g., D mean and V20% [38] . For its use in online-adaptive, conventional radiotherapy (RT) under image guidance, such as MR-guided RT (MRgRT), computational speed could also be crucial [39] .…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, only a limited number of treatment planning studies have investigated the clinical benefits associated with onboard MRI guidance for proton therapy. Moreover, these studies, which encompassed pediatric (Acharya et al 2020), liver (Moteabbed et al 2021a), prostate (Moteabbed et al 2021b), and lung cancer patients (Rabe et al 2023), did not consider the effect of the magnetic field on the proton dose distributions. In another study, Kurz et al (2017) used MC-based treatment planning to investigate the robustness against setup errors and anatomical changes for prostate treatment plans optimised with and without a magnetic field.…”
Section: Introductionmentioning
confidence: 99%